Electrical principles [ (Electricity and electronics, 2006)
"This live-action video introduces the basics of electricity. Computer animation adds interest and excitement as the video comes to life in its coverage of atoms, conductors, insulators, free electrons, voltage, current, resistance, magnetism, attraction-repulsion, electromagnets, a simple circuit, and other electrical principles. Ideal for courses in electricity, physics, science, automotive, and technology."--Container